Disease relapses in multiple sclerosis can be influenced by air pollution and climate seasonal conditions - Vojinović, Slobodan; Savić, Dejan; Lukić, Stevo; Savić, Ljiljana; Vojinović, Jelena (Vojnosanitetski pregled, 2014)
Background/Aim. Environmental factors may influence the disease activity in patients with relapsing-remitting multiple sclerosis (MS). The aim of this study was to evaluate the influence of air pollution and seasonal climate factors of any on number of relapses in MS patients during a consecutive 5 years of observation. Methods. We retrospectively analyzed data of MS patients from the town of Niš, hospitalized at the Clinic of Neurology, Clinical Center Niš, Serbia, from 2005 to 2009. Climate data: mean daily sun shining; mean monthly sun shining, mean whole daily cloudiness, daily cloudiness at 7 a.m, 2 p.m. and 9 p.m. and air pollution expressed by NSR (New Source Review) were obtained from the Meteorology Observatory Niš. Results. During a 5-year of observation there were 260 relapses in 101 MS patients. The number of relapses showed a significantly negative correlation with the number of days with NSR
Keywords: multiple sclerosis; recurrence; air pollution; climate; sunlight; vitamin d